Analisis QoS Streaming Video Jaringan MPLS dan VPLS - Novaldy Refi Nugita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Video streaming is a medium that has many benefits, especially for education, online meetings, or just to watch movies. The development of the internet network over the years can make it easier to access video streaming. MPLS is one of the internet networks that is used because it is fast in transferring data so that accessing video streaming becomes easier and MPLS is also the basic network for the formation of a VPLS network. MPLS applies labeling to a data packet that can increase the speed in the process of sending data on the network. There is also something called VPLS in the internet network which has almost the same principle as MPLS. Of the two networks mentioned, a trial will be conducted using video streaming with QoS parameters including throughput, delay, and packet loss. The final result of this research is a comparison of the QoS performance of the MPLS network and the VPLS network.